An application of recent developments of Data Envelopment Analysis to the evaluation of secondary schools in Portugal. (1st January 2001) - Santos, Jorge; Themido, Isabel
This paper highlights the potentialities of Data Envelopment Analysis to evaluate the performance of organisations, using the concept of super-efficiency - an extension of DEA which increases its performance - and presents an example from the public sector to illustrate the method. The example selected is that of a school network where a place in a school can be seen as a perishable good, as places which are not occupied during an academic year are wasted. Results for the Portuguese Secondary school network show that the average efficiency of overcrowded schools, that is, those exceeding their capacity, is lower than that of schools which are less crowded. This shows clearly that overcrowded schools, on average, are less efficient in transforming their inputs into academic performance. It is this conviction, seldom proved scientifically, which leads governments and international organisations to recommend planning criteria for public facilities.